Peningkatan Kemampuan Berhitung Melalui Permainan Kartu Uhipa Pada Anak Kelompok B - Renni Agustiningsih; Octavian Dwitanto (NANAEKE: Indonesian Journal on Early Childhood Education, 2023)
This study aims to determine effectiveness out whether the Uhipa card game improves numercy skills of children in group B. Learning activities for erly childhood usually involve playing. Numeracy activities are the basis of human communication, therefore the ability to count is very important to be taught from an early age. If children do not understand numeracy properly, it can hinder their interaction with individuals or groups. However, observation of 20 children in the Dharma Wanita Kindergarden Pacing group B shows that the ability to count is not yet developed. Therefore the researcher developed a new innovation in the form of the Uhipa card game. The Uhipa card game uses media in the form of number card and picture cards made of thick cardboard which are easy to find the area to be examined. This Uhipa card game is a new game innovation to improve children’s numeracy skills. Action research refers to the classroom action research model Kemmis and Mc. Taggart (planning, action, observation, reflection). Based on the validation results, the Uhipa card gamehas a validity percentage of 85%, which is within the achievement criteria of 75% - 100%, indicating that the game is highly valid and can be used without revision